Cultivo de sorgo sacarino no semiárido: produção, qualidade de fitomassa, etanol e sementes em função da variedade e arranjo espacial - Silva, Tatiana Maria da (2018)
Sweet sorghum is a very promising alternative for the production of ethanol, and can be harvested during the off-season of sugarcane. Several cultural practices are important in plant production. Among them, choosing the best plant arrangement is important because it favors greater efficiency in the use of environmental resources, such as light and water, and the control of invasive plants. The objective of this experiment was to evaluate the growth, productivity and quality of the broth of two varieties of sorghum, in addition to the production and quality of seeds as a function of different spacings between lines and between plants. For that, an experiment was conducted at the Curu Valley Experimental Farm belonging to the Federal University of Ceará, Pentecoste - CE, with two agricultural cycles (2015 and 2016) in the rainy season. The BRS 506 and SF 15 varieties were used, and the spacings between the lines (50, 60, 70 and 80 cm) and between plants (8, 12 and 16 cm) were studied. The mean values for the morphological growth of the plants showed that the highest height was observed at 90 DAS (328.11 cm) and that the diameter of the stem was favored at the 70 cm spacing, where it presented 15.59 mm. For the phytomass production, higher values were observed for the BRS 506 variety, in the first cycle. The smaller line spacing used provided the higher MST values in both cycles, ie 34.6 and 16.2 t ha-1, respectively. Among the studied varieties, the best performance in relation to broth yield was for BRS 506, which presented a mean of 12.01 m³ ha-1. The BRS 506 variety presented a mean of 140.02 g L-1 of CST, with average yield of 4,157.85 L ha-1 ethanol in the first cycle. Regarding the quality of the seeds, it was verified that both the variety and the arrangement of the plants affected them physiologically. The sorghum presents better phytomass productivity when handling in the spacing of 50 cm between the lines and 8 cm between plants, making a population of 250 thousand plants per hectare. The same crop spacing is recommended for yield and broth quality in the semi-arid Northeast. However, for seed production, sorghum (BRS 506) plants should be managed in the largest spacing studied, 80 cm between the lines and 16 cm between plants to obtain seeds with higher development and vigor.